Deficiency of C3a receptor attenuates the development of diabetic nephropathy - Ming-hui Zhao; Xiao-Qian Li; Dong-Yuan Chang (BMJ Open Diabetes Research & Care)
Objective Diabetic nephropathy (DN) is the leading cause of chronic kidney disease and end-stage renal disease. Emerging evidence suggests that complement activation is involved in the pathogenesis of DN. The aim of this study was to investigate the pathogenic role of C3a and C3a receptor (C3aR) in DN.Research design and methods The expression of C3aR was examined in the renal specimen of patients with DN. Using a C3aR gene knockout mice (C3aR−/−), we evaluated kidney injury in diabetic mice. The mouse gene expression microarray was performed to further explore the pathogenic role of C3aR. Then the underlying mechanism was investigated in vitro with macrophage treated with C3a.Results Compared with normal controls, the renal expression of C3aR was significantly increased in patients with DN. C3aR−/− diabetic mice developed less severe diabetic renal damage compared with wild-type (WT) diabetic mice, exhibiting significantly lower level of albuminuria and milder renal pathological injury. Microarray profiling uncovered significantly suppressed inflammatory responses and T-cell adaptive immunity in C3aR−/− diabetic mice compared with WT diabetic mice, and this result was further verified by immunohistochemical staining of renal CD4+, CD8+ T cells and macrophage infiltration. In vitro study demonstrated C3a can enhance macrophage-secreted cytokines which could induce inflammatory responses and differentiation of T-cell lineage.Conclusions C3aR deficiency could attenuate diabetic renal damage through suppressing inflammatory responses and T-cell adaptive immunity, possibly by influencing macrophage-secreted cytokines. Thus, C3aR may be a promising therapeutic target for DN.